ВПЛИВ ФОРМИ ПОЛЮСІВ ЕЛЕКТРОМАГНІТНОГО АКТУАТОРА ПОСТІЙНОГО СТРУМУ НА ЙОГО ТЯГОВУ ХАРАКТЕРИСТИКУ - Grechko, O.M. (Інститут електродинаміки НАН України, Київ, 2024)
Many technical objects use the electromagnetic DC actuators, which, unlike AC actuators, are more reliable, simpler in terms of manufacturing technology and have greater wear resistance. The listed advantages are the reason for the significant use of DC actuators in various industries including application as drive mechanisms of electrical devices. The DC actuator as a part of any technical object almost always plays one of the main roles from the point of view of reliable operation of entire device. Therefore the question of studying the designs of actuators and their characteristics is a rather topical task. Three designs of forward-moving electromagnetic DC actuators with the same overall dimensions and winding data are studied. They differ in the shapes of the supporting surfaces of poles, in other words, the surfaces with flat, conical and cut-conical shapes. As established, the shape of the supporting surfaces of poles has a significant impact on the thrust characteristics of the actuator and depending on the length of air gap this effect has a different character. The patterns of magnetic field of the studied actuators with an attracted armature are constructed, and the nature of magnetic field distribution and magnetic flux density distribution in operated gap are evaluated. The nature of the influence of cutting angle on static thrust characteristic for actuators with conical and cut-conical pole shapes is studied too. References 21, table 1, figures 7.